Awareness of HIV/AIDS and its routes of transmission as well as access to health knowledge among rural residents in Western China: a cross-sectional study - Tianqi Zhang; Yang Miao; Lingui Li; Ying Bian (BMC, 2019)
Abstract Background The purpose of this study was to evaluate the coverage of HIV health education among rural residents in western China by ascertaining their awareness of HIV/AIDS and its transmission routes, and to investigate how these residents receive health information. Methods A survey was conducted through stratified clustered sampling at 99 county hospitals in 11 provinces in western China. Information was collected on awareness of HIV/AIDS and its transmission routes, as well as residents' access to health knowledge. Chi-square analysis was used to analyse the differences in HIV/AIDS awareness (knowing of the existence of HIV/AIDS, hereinafter referred to as "HIV awareness rate") between different subgroups categorized by demographic status, regional factors, and different methods of access to health knowledge. To further analyse the effects of access to health knowledge on HIV awareness, a logistic regression model was established. The relationship between access to health knowledge and transmission routes was also examined using chi-square analysis. Results The HIV awareness rate of the total 9274 participants was 80.9%. There were statistically significant differences between subgroups classified by age (χ 2 = 482.118, p<0.001), education (χ 2 = 853.465, p<0.001), occupation (χ 2 = 340.553, p<0.001), income (χ 2 = 186.448, p<0.001), cumulative HIV cases according to province (χ 2 = 59.513, p<0.001), per capita annual net income of rural households according to province (χ 2 = 64.676, p<0.001), proportion of minority population according to province (χ 2 = 94.898, p<0.001), direct access to health knowledge (medical staff: χ 2 = 419.775, p<0.001; mass media: χ 2 = 740.238, p<0.001; family members: χ 2 = 12.189, p<0.001; socializing: χ 2 = 48.780, p<0.001; health education activities: χ 2 = 154.400, p<0.001), and indirect access to health knowledge (having a non-communicable disease with medical instructions χ 2 = 78.709, p<0.001; physical examinations: χ 2 = 135.679, p<0.001). The logistic regression model showed that education and mass media had the strongest impacts on HIV awareness among all methods of access. Participants had the least awareness of HIV's mother-to-child transmission route. Conclusion The HIV awareness rate indicated that previous HIV health education covered 80% of the rural population in western China. Mass media should take greater responsibility in HIV health education for the general population, and special attention should be paid to the elderly, the most impoverished population, minority community as well as the mother-to-child transmission route.